The Role of Sharia Banking in the Development of the Halal Tourism Industry in Indonesia: Opportunities and Challenges in Bengkulu Province - suharyono, suharyono; Suyono, Suyono; Yanto, Syafri; Azmi, Muhammad (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to examine the role of Islamic banking in the development of halal tourism in Indonesia, with a particular focus on identifying both opportunities and challenges.Design/Methodology: This research employs a qualitative approach with a descriptive-analytical method. The study is based on a literature review and analyzed through several stages, including classification, reduction, and verification of sources related to halal tourism.Findings: The findings indicate that Islamic banking holds a pivotal role in advancing halal tourism by providing financing, facilitating sharia-compliant financial services, and fostering synergies with related halal industries. Nonetheless, limited public awareness and competition with conventional banks remain significant challenges to its optimal contribution.Practical Implications: The study highlights that Islamic banking can play a strategic role in financing and supporting halal tourism businesses, particularly by addressing capital constraints. Strengthening collaboration and innovative sharia-compliant financial products will enhance the growth and sustainability of halal tourism in IndonesiaOriginality/Value: This research contributes originality by examining the intersection of Islamic banking and halal tourism within the specific context of Bengkulu Province, a locus rarely addressed in prior studies. The study advances the discourse by positioning Islamic banking not merely as a financing intermediary but as a structural enabler of halal tourism development, thereby offering a novel perspective on its role in regional economic empowerment and sustainable industry growth